Discrete time models of entry intro marriage based on retrospective marital histories of young adults in the United States and the Federal Republic of Germany - James C. Witte (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
This paper identifies and quantifies the social processes that account for the well-known relationship between chronological age and entry into marriage. Patterns of entry into marriage, broken down by sex, year of birth and level of schooling, are usea to estimate year to year fluctuations in the available pool of marriage partners. Age-related variation in entry into marriage is then considered in light of changes in the marriage pool as well as labor force integration - captured through current and lagged measures of employment and enrollment status. The analysis rests on data from the 1984 panel of the united States Census Bureau's Survey of Income and Program Participation (SIPP) and the German Socio-Economic Panel (SOEP).
Keywords: 330